Irritable bowel syndrome: Is it “irritable brain” or “irritable bowel”? - Padhy, Susanta Kumar (J Neurosci Rural Pract, 2015)
Irritable bowel syndrome (IBS) has been recognized as one of the most common and best studied disorders among the group of functional gastrointestinal disorders. It is a functional bowel disorder in which abdominal pain or discomfort is associated with defecation or a change in bowel habit. In the Western world, IBS appears to affect up to 20% of the population at any given time but in Asian countries, the median value of IBS prevalence defined by various criteria ranges between 6.5% and 10.1%, and community prevalence of 4% is found in North India. Those attending gastroenterology clinics represent only the tip of the iceberg. The disorder substantially impairs the quality of life, and the overall health-care costs are high. IBS has therefore gained increased attention from clinicians, researchers, and pharmaceutical industries. It is often frustrating to both patients and physicians as the disease is usually chronic in nature and difficult to treat. However, the understanding of IBS has been changing from time to time and still most of its concepts are unknown. In this review we have discussed, debated, and synthesized the evidence base, focusing on underlying mechanisms in the brain and bowel. We conclude that it is both brain and bowel mechanisms that are responsible. The clinical implication of such mechanisms is discussed.